2005
DOI: 10.1080/15320380590954051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immobilizing Substances and Salinity on Heavy Metals Availability to Wheat Grown on Sewage Sludge-Contaminated Soil

Abstract: The objective of the investigation was to evaluate the effect of immobilizing substances and NaCl salinity on the availability of heavy metals: Zn, Cd, Cu, Ni, and Pb to wheat (Triticum aestivum L.). In greenhouse pot experiment, a sewage sludge amended soil was treated with the following immobilizing substances: three clay minerals (Na-bentonite, Ca-bentonite and zeolite), iron oxides (goethite and hematite), and phosphate fertilizers (superphosphate and Novaphos). The pots were planted with wheat and were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 51 publications
(66 reference statements)
1
29
0
1
Order By: Relevance
“…Sari and Din (2012) recently recognized that higher heavy metal accumulation under saline conditions was related to the maintenance of cell osmosis mechanisms by plants. Usman et al (2005) found that increased concentration of Pb in wheat shoot in the presence of salinity were the result of increased Pb mobility and availability due to the formation of Pb-Cl complexes. Under saline conditions, the Cl − more considerably increased the mobility of Pb than SO 4 2− due to the formation of soluble ion pairs like PbCl + (Acosta et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sari and Din (2012) recently recognized that higher heavy metal accumulation under saline conditions was related to the maintenance of cell osmosis mechanisms by plants. Usman et al (2005) found that increased concentration of Pb in wheat shoot in the presence of salinity were the result of increased Pb mobility and availability due to the formation of Pb-Cl complexes. Under saline conditions, the Cl − more considerably increased the mobility of Pb than SO 4 2− due to the formation of soluble ion pairs like PbCl + (Acosta et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Acosta et al (2011) reported that the soil salinity resulted in enhanced heavy metal mobilization. This can be due to the reasons that heavy metals complex formation occurred with highly mobile inorganic ligands such as Cl − in soil solution (Usman et al, 2005). The subsequent association has a lesser positive charge than the free metal ions, and may be uncharged or carry a net negative charge, thereby has higher metal mobility (McLean and Bledsoe, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations